Good Practices of Inclusive Innovation in Creative and Cultural Enterprises for Inclusive Growth - Méndez Velásquez, Lina Marcela; Villa Enciso, Eliana María; Valencia-Arias, Alejandro (Semestre Económico, 2021)
The objective of this article is to identify good practices for inclusive innovation in creative and cultural industry ventures for inclusive growth. The methodology used is based on a comparative analysis, selecting as references five case studies of inclusive innovation in creative and cultural ventures. The analysis of the results presents a comparative matrix according to seven critical success factors proposed: people (included ways in which these people are included), inclusion activities, value proposition of the enterprise, type of technology or innovation applied, role of government and value proposition of the enterprise. The findings indicate that creative and cultural ventures are characterized by being historically excluded, impact and consumption of an innovation or technology, with simple inclusive businesses that seek the solution to a problematic for its population, where the business can arise both from a state-of-the-art technology and from a pre-existing one and orient its value proposition towards a social objective.